Building an inclusive community of learners by centering a strong culture of care in large lecture classes - Audette, Dylan S.; Bennett, Shauna; Chan, Mun Chun; Chapman, Dail; Elmendorf, Heidi; Floyd, Jeanetta (Frontiers in Education, 2023)
Foundational and early university STEM courses are usually taught as large lecture courses. For many students, especially students from marginalized identity groups, a large course can be an impersonal experience that leaves students with a low sense of belonging, negatively impacting academic performance and retention in the discipline. In this paper, we present specific interventions and practices–cultivated through years of intentional iteration by multiple faculty–to build a community of learners that care for one another in a large foundational Biology course. We define our “culture of care” as building and maintaining a class structure and climate that empowers students to form relationships that provide emotional support and meet affective needs. We believe this allows students to persist and succeed in the course, and helps to build an understanding of how course material will lead to achievement of their intrinsic academic and career goals. We believe these interventions and practices leverage the unique benefits of large class sizes, including the diversity of students present and the power of shared positive group experiences. In this paper, we describe key aspects of the current course, including (1) pedagogical choices that help students invest in their learning and focus on key scientific skills, (2) training faculty and undergraduate assistant members of the teaching team to build a community that cares, and (3) designing assignments that focus on well-being and teamwork. Throughout this paper, we hope to provide a template that can be adapted to different disciplines and institutions for designing large lecture courses that are inclusive, engaging, and emotionally supportive.